Increasing Efficiency and Effectiveness through Digitalization in Batik Cooperative Business Processes (Kombas) - Edward Edward; Michaelli Sugianto; Julius Sutrisno (Jurnal Indonesia Sosial Teknologi, 2024)
In company operations, of course, records in the form of stock data and transaction data are needed to make reports. Likewise, KOMBAS has still used manual recording so there are still many shortcomings that cause cooperative operations to be not optimal. The method used is a waterfall methodology consisting of needs analysis, system design, and testing. The type of research used is qualitative research by conducting an interview process with a resource person, namely the chairman of the Bekasi Batik Cooperative (KOMBAS). The results of the project are an analysis of business flows, system flows, and business models, and then the final result is a website-based application design that has various features according to the company's needs. The features available in the application include goods data, supplier data, customer data, employee data, and transaction data (sales, purchases, and returns). These features, in addition to being able to enter data, also have access to update and delete. This project concludes that the design of a website-based inventory application will certainly provide efficiency and productivity for cooperatives that provide automation processes, smoother workflows, and faster access to information so that it can save time, costs, and resources, and improve service quality.